Decision Making Model for Analysis of Culinary Intangible Cultural Heritage Tourism Resources: Forest HyperSoft Set and Results - Chunpeng Liu; Ling Chen (Neutrosophic Sets and Systems)
Culinary intangible cultural heritage plays a pivotal role in preserving the authenticity and uniqueness of a region’s traditions while serving as a driving force for tourism development. The evaluation of culinary intangible cultural heritage tourism resources is essential to ensure that such traditions are not only recognized but also sustained for future generations. This study presents a comprehensive framework for assessing the value of culinary heritage through multiple criteria, including cultural significance, economic impact, gastronomic appeal, sustainability, and policy support. By utilizing a multi-criteria decision-making (MCDM) approach, this evaluation aims to provide a structured methodology for ranking and analyzing different culinary traditions worldwide. We use the Forest HyperSoft set to divide each criterion as a TreeSoft set. Then in each TreeSoft set we can compute the criteria weights by MEREC method and rank the alternatives by the MARCOS method. This study uses four main criteria and six sub criteria with values. We have four TreeSoft sets. The results are shown in each TreeSoft set.